Research Progress of “Healthy in China” 2030 Strategy—Based on Citespace’s Visualized Knowledge Graph Analysis - Li ZHANG, Xiaowan SONG, Hao ZHANG (Forest Chemicals Review, 1970)
Since the 2016 Government of china reviewed and approved the "Healthy in China 2030" Planning Outline, "Healthy in China" has become a hot spot for theoretical research, and a large number of academic research results have emerged. Using the academic papers related to the “Healthy in China” strategy included in the CSSCI full-text database from 2016 to 2021 as the data source, the document visualization analysis software CiteSpace was used to construct the author's cooperative relationship network, the keyword co-occurrence network, and the hotspot knowledge timeline graph to refine the “Healthy in China” aspect In order to grasp the overall context of relevant research on “Healthy in China” at this stage, and provide references for the future trend of relevant research on “Healthy in China”.